Investigating the Role of Osteopontin (OPN) in the Progression of Breast, Prostate, Renal and Skin Cancers - Gautam Kundu; Selvakumar Elangovan (Biomedicines)
Background/Objectives: Cancer is caused by disruptions in the homeostatic state of normal cells, which results in dysregulation of the cell cycle, and uncontrolled growth and proliferation in affected cells to form tumors. Successful development of tumorous cells proceeds through the activation of pathways promoting cell development and functionality, as well as the suppression of immune signaling pathways; thereby providing these cells with proliferative advantages, which subsequently metastasize into surrounding tissues. These effects are primarily caused by the upregulation of oncogenes, of which SPP1 (secreted phosphoprotein 1), a non-collagenous bone matrix protein, is one of the most well-known. Methods: In this study, we conducted a further examination of the transcriptomic expression profile of SPP1 (Osteopontin) during the progression of cancer in four human tissues, breast, prostate, renal and skin, in order to understand the circumstances conducive to its activation and dysregulation, the biological pathways and other mechanisms involved as well as differences in its splicing patterns influencing its expression and functionality. Results: A significant overexpression of SPP1, as well as a set of other highly correlated genes, was seen in most of these tissues, indicating their extensive implication in cancer. Increased expression was observed with higher tumor stages, especially in renal and skin cancer, while applying therapeutic modalities targeting these genes dampened this effect in breast, prostate and skin cancer. Pathway analyses showed gene signatures related to cell growth and development enriched in tumorigenic conditions and earlier cancer stages, while later stages of cancer showed pathways associated with weakened immune response, in all cancers studied. Moreover, the utilization of therapeutic methods showed the activation of immunogenic pathways in breast, prostate and skin cancer, thereby confirming their viability. Further analyses of differential transcript expression levels in these oncogenes showed their exonic regions to be selectively overexpressed similarly in tumorigenic samples in all cancers studied, while also displaying significant differences in exon selectivity between constituent transcripts, providing a basis for their high degree of multifunctionality in cancer. Conclusions: Overall, this study corroborates the entrenched role of SPP1 in the progression of these four types of cancer, as confirmed by its overexpression and activation of related oncogenes, their co-involvement in key cellular pathways, and predisposition to exhibit differential splicing between their transcripts, while the above effects were found to be highly inhibitable through treatment methods, thereby highlighting its promising role in therapeutic development.